Consumer responses to on-site Olympic sponsorship activation: the impact of interactivity, emotions, and perceived image fit on brand attitude formation. (2014) - Kim, Ari; Kaplanidou, Kyriaki
On-site sponsorship activations have become more prominent in executing a mega-sport event sponsorship program. The current study investigates factors that drive consumers' attitudes towards on-site sponsorship activation and sponsor brand. In particular, this study examines the relationships among interactivity, emotions, fit between on-site sponsorship activation and event, attitude towards on-site sponsorship activation, and attitude towards the sponsor brand. Data were obtained from 205 spectators of the 2012 London Olympic Games who experienced at least one sponsorship activation on-site. The results suggested that interactivity is a significant predictor of arousal, and in turn, arousal increases pleasure. Pleasure and high sponsor-event fit influence attitude towards on-site sponsorship activation, which eventually influences attitude towards sponsor brand. The relationship between fit and attitude towards brand was mediated by attitude towards on-site sponsorship activation suggesting the value of on-site activations for brand equity. The theoretical and managerial implications are discussed along with limitations and future directions for research.